KAJIAN YURIDIS ANGGARAN DISABILITAS DALAM KEUANGAN NEGARA - B. Hengky Widhi A.; Y. Sri Pudyatmoko (Universitas Lampung, 2015)
This study is departed from the idea that the provision of budget for the persons with disabilities is a very important thing. Recalling this problem, a good regulation is required. This study raised a problem of the urgency of budgeting for the persons with disabilities and the funding strategy as well as the juridical strategy in governing the budget for the persons with disabilities. This study employed a juridical analytical method, a research which is conducted to analyze certain provision of law to be used later in answering the society’ problem. From the research, it could be found that the provision of fund to provide the infrastructures for the persons with disabilities is very urgent. Such urgency included the reasons concerning the funding provision for the persons with disabilities and the determination of their needs required the funding provision. The budgeting strategy for the persons with disabilities is highly dependent on who is responsible for the affairs concerning the persons with disabilities. In the context of the relationship division between Central Government and Local Government, it includes those decentralized to local areas. For that reason, the local areas could provide it from Local Original Income (PAD) deriving from Entertainment Tax with earmarking pattern. When it was not sufficient, recalling that the existing local tax potential was inadequate or null, the funding for the persons with disabilities could be provided by Central Government and the other legitimate source of funds. The regulation strategy which should be taken is to amend the Law Number 28 of 2009 and Law Numer 40 of 2007 on Corporate Social Responsibility, to establish the Law of the Persons with Disabilities to govern the funding.Keywords: persons with disabilities, budget, state finance